Secondary School Science Teacher Response to Minimum Competency Assessment: Challenges and Opportunities - Sri Yamtinah; Budi Utami; Mohammad Masykuri; Bakti Mulyani; Maria Ulfa; Ari Syahidul Shidiq (Jurnal Penelitian Pendidikan IPA, 2022)
Teachers have an essential role in preparing students for Minimum Competency Assessment (MCA) or Asesmen Kompetensi Minimum (AKM). It takes preparation, readiness, and a good teacher's perception of the AKM so that the implementation of this program goes well. This study aims to analyze teachers' perceptions in secondary schools related to the opportunities and challenges of implementing AKM. A total of 66 secondary school science teachers participated as respondents in this study. Respondents in this study were randomly selected based on their willingness to fill out a given survey. The data collection instruments were six open-ended questions. This instrument is distributed online using Google Forms. The data obtained were then analyzed qualitatively and quantitatively. The results of this study reveal that the majority of science teachers have the perception that AKM policy is appropriate and suitable for implementation. However, the availability of supporting facilities and ICT literacy of students and teachers is considered a challenge that must be met. On the other hand, AKM and National Assessment (NA) are considered opportunities to improve the quality of education both nationally and locally in schools. This research is expected to reference the perception of science teachers about the challenges and opportunities for implementing AKM policies in junior high schools